Escherichia coli O26 in feedlot cattle: Fecal prevalence, isolation, characterization, and effects of an E. coli O157 vaccine and a direct-fed microbial - Paddock, Zachary Dean; Renter, David G.; Cull, Charley A.; Shi, Xiaorong; Bai, Jianfa; Nagaraja, Tiruvoor G. (My University, 2014)
Escherichia coli O26 is second only to O157 in causing foodborne, Shiga toxin–producing E. coli (STEC) infections. Our objectives were to determine fecal prevalence and characteristics of E. coli O26 in commercial feedlot cattle (17,148) that were enrolled in a study to evaluate an E. coli O157:H7 siderophore receptor and porin (SRP®) vaccine (VAC) and a direct-fed microbial (DFM; 106 colony-forming units [CFU]/animal/day of Lactobacillus acidophilus and 109 CFU/animal/day of Propionibacterium freudenreichii). Cattle were randomly allocated to 40 pens within 10 complete blocks; pens were randomly assigned to control, VAC, DFM, or VAC+DFM treatments. Vaccine was administered on days 0 and 21, and DFM was fed throughout the study. Pen-floor fecal samples (30/pen) were collected weekly for the last 4 study weeks. Samples were enriched in E. coli broth and subjected to a multiplex polymerase chain reaction (PCR) designed to detect O26-specific wzx gene and four major virulence genes (stx1, stx2, eae, and ehxA) and to a culture-based procedure that involved immunomagnetic separation and plating on MacConkey agar. Ten presumptive E. coli colonies were randomly picked, pooled, and tested by the multiplex PCR. Pooled colonies positive for O26 serogroup were streaked on sorbose MacConkey agar, and 10 randomly picked colonies per sample were tested individually by the multiplex PCR. The overall prevalence of E. coli O26 was higher (p<0.001) by the culture-based method compared to the PCR assay (22.7 versus 10.5%). The interventions (VAC and or DFM) had no impact on fecal shedding of O26. Serogroup O26 was recovered in pure culture from 23.9% (260 of 1089) of O26 PCR-positive pooled colonies. Only 7 of the 260 isolates were positive for the stx gene and 90.1% of the isolates possessed an eaeβ gene that codes for intimin subtype β, but not the bfpA gene, which codes for bundle-forming pilus. Therefore, the majority of the O26 recovered from feedlot cattle feces was atypical enteropathogenic E. coli, and not STEC.
Keywords: E. coli O26; Shiga toxin-producing E. coli; Cattle; Feces